Implementasi Open Source Enterprise Resource Planing (ERP) ODOO Pada PMB Universitas Bhayangkara Jakarta Raya - iskandar, rudi; Syahroni, Muhammad; Yunizar Pratama Yusuf, Ajif (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2025)
Currently, Information and Communication Technology is developing rapidly, including in the field of education. In general, technology is used to process data, which includes processing, obtaining, compiling, storing, and manipulating data in various ways and procedures to produce high-quality information. Universities must continue to improve their services to meet the needs of the academic community in order to continue to exist. The rapid development of technology and information in the field of education also triggers fierce competition, especially when accepting new students every academic year. Universitas Bhayangkara Jakarta Raya (Ubhara Jaya), one of the private universities in Bekasi City, routinely carries out the new student admission process (PMB) at the beginning of each academic year. This process is managed by a marketing team that must handle many applicants, remind prospective students about the entrance exam time, and manage the re-registration and payment process. All of this requires an adequate system to meet the needs of universities and applicants. Management also needs reports that can be used to determine promotional strategies based on the results of new student admissions. With the implementation of Odoo, it is expected to increase efficiency in data processing, analysis, reporting, and evaluation of new student admissions.